2017
DOI: 10.1007/s11103-017-0644-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a peroxidase gene (AtPrx64) of Arabidopsis thaliana in tobacco improves plant’s tolerance to aluminum stress

Abstract: AtPrx64 is one of the peroxidases gene up-regulated in Al stress and has some functions in the formation of plant second cell wall. Its overexpression may improve plant tolerance to Al by some ways. Studies on its function under Al stress may help us to understand the mechanism of plant tolerance to Al stress. In Arabidopsis thaliana, the expressions of some genes (AtPrxs) encoding class III plant peroxidases have been found to be either up-regulated or down-regulated under aluminum (Al) stress. Among 73 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 64 publications
0
51
0
Order By: Relevance
“…The use of expression studies, biochemical characterization and mutants or transgenic plants has been very useful to assign a precise function to a specific Prx ( Cosio and Dunand, 2009 ). Plant transformation has provided numerous evidences of the in planta function of various isoenzymes ( El Mansouri et al, 1999 ; Kawaoka et al, 2003 ; Kim et al, 2008 ; Herrero et al, 2013a ; Fernández-Pérez et al, 2014 , 2015 ; Cosio et al, 2017 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of expression studies, biochemical characterization and mutants or transgenic plants has been very useful to assign a precise function to a specific Prx ( Cosio and Dunand, 2009 ). Plant transformation has provided numerous evidences of the in planta function of various isoenzymes ( El Mansouri et al, 1999 ; Kawaoka et al, 2003 ; Kim et al, 2008 ; Herrero et al, 2013a ; Fernández-Pérez et al, 2014 , 2015 ; Cosio et al, 2017 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that AtPrx66 and AtPrx47 were associated with lignification of vessels, whereas AtPrx64 was associated with lignification of sclerenchyma [ 30 , 31 ]. A recent study demonstrated that aluminum tolerance of tobacco ( Nicotiana tabacum L.) plants was improved by overexpression of a tprx64 [ 32 ].…”
Section: Membrane-bound Class III Peroxidasesmentioning
confidence: 99%
“…[63]. In tobacco, it has been showed that overexpression of a class III PRX gene (AtPrx64) of A. thaliana improved the plant's aluminum tolerance by increasing the root growth and scavenging accumulation of aluminum and ROS [64]. In A. thaliana, overexpression of AtPRX3 was shown to improve the dehydration and salt tolerance.…”
Section: The Evolution Of T Aestivum Taprx-2amentioning
confidence: 99%